2024
DOI: 10.1029/2023jd039492
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lightning Flash Rate Parameterizations in a Cloud‐Resolved WRF‐Chem Simulation of the 29–30 May 2012 Oklahoma Severe Supercell System Observed During DC3

K. A. Cummings,
K. E. Pickering,
M. C. Barth
et al.

Abstract: Eighteen lightning flash rate parameterization schemes (FRPSs) were investigated in a Weather Research and Forecasting model coupled with chemistry cloud‐resolved simulation of the 29–30 May 2012 supercell storm system observed during the Deep Convective Clouds and Chemistry (DC3) field campaign. Most of the observed storm's meteorological conditions were well represented when the model simulation included both convective damping and lightning data assimilation techniques. Newly‐developed FRPSs based on DC3 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 122 publications
(284 reference statements)
0
12
0
Order By: Relevance
“…The ICEFLUX scheme is based on the upward flux of cloud ice at 440 hPa. However, Cummings et al (2024) found that for this storm evaluating the flux at 390 hPa produced a better comparison with observed flash rates. Figure 1 shows the time series of flash rates produced by the modified ICEFLUX scheme over this time period.…”
Section: 1029/2023jd039439mentioning
confidence: 83%
See 4 more Smart Citations
“…The ICEFLUX scheme is based on the upward flux of cloud ice at 440 hPa. However, Cummings et al (2024) found that for this storm evaluating the flux at 390 hPa produced a better comparison with observed flash rates. Figure 1 shows the time series of flash rates produced by the modified ICEFLUX scheme over this time period.…”
Section: 1029/2023jd039439mentioning
confidence: 83%
“…These peaks of roughly 100, 300, 800, and 2,200 total flashes 10-min 1 occurred at 22:00, 22:50, 23:50, and 01:00 UTC. Following the primary peak, the observed flash rate decreased at a faster rate than it increased (see Cummings et al, 2024). The 29-30 May 2012 convection contained high flash rate supercells with small flash extents (Barth et al, 2015).…”
Section: Lightning and Nomentioning
confidence: 94%
See 3 more Smart Citations